MacCormick's Scotland - Walker, Neil, 1960- (Edinburgh studies in law, 2012)
This book analyses in depth the distinctively Scottish themes in the work of Sir Neil MacCormick, the world-renowned legal philosopher and prominent Scottish public intellectual who died in 2009 after holding the Regius Chair in Public Law and the Law of Nature and Nations at Edinburgh University for 36 years. MacCormick's work, and works about MacCormick, attract both a domestic and an international audience. Readers will gain an understanding of how MacCormick's Scottish roots, interests and commitments coloured his work - both his distinctively Scottish writings and the overall intellectual outlook that informed his broader legal and philosophical writings. The book provides a well rounded appreciation of the Scottish dimension in MacCormick's thinking and writing. It focuses on a number of prominent Scottish themes in MacCormick's work and life and is structured around four key themes: 1) the nature and identity of a legal system; 2) sovereignty, European integration and Scottish independence; 3) the legacy of the legal and political thought of the Scottish enlightenment; and 4) the role of the academic in the Scottish public sphere. Key Features:* Edited by Neil Walker - a highly respected scholar and thinker, and a prolific writer who has edited many excellent collections of essays.* The editor succeeded MacCormick in the Regius Chair and all of the contributors are closely acquainted with MacCormick the man and the scholar.* The first book to examine MacCormick through a distinctly Scottish lens.